Waste to Wealth: Chemical Recycling and Chemical Upcycling of Waste Plastics for a Great Future - Chen, Huan; Wan, Kun; Zhang, Yayun; Wang, Yanqin (ChemSusChem, 2021)
The linear approach to resource utilization has led to the accumulation of waste plastic in the environment for decades. Unfortunately, both traditional mechanical recycling and incineration have faced their bottlenecks that have always resulted in quality deterioration and value recovery failures. Recently, chemical recycling and upcycling processes, including the conversion of plastics into their virgin monomers, liquid fuels, or chemical feedstocks to produce value‐added products, have been identified as the most promising strategy for recovering value from waste plastics. However, these methods are often cost prohibitive and relying on stringent conditions compared to current recycling methods. Accordingly, this Minireview summarizes recent trends and achievements in the chemical recycling and upcycling of waste plastics. We highlight three research topics: depolymerization of plastics into monomers; degradation of plastics into liquid fuels and waxes; and conversion of plastics into hydrogen, fine chemical feedstocks, and value‐added functional materials. Indeed, chemical recycling and upcycling is a bright path to a circular and environmentally friendly plastic economy. The lighter side of waste plastics: Chemocatalytic strategies that give life to value‐added Chemicals, fuels, and monomers hold the promise of transforming plastic crisis, which is barely addressed by mechanical recycling and incineration, into an opportunity. This Minireview aims to summarize emerging trends in catalytic chemical recycling and upcycling of waste plastics into chemicals, fuels, or products with higher values, particularly regarding methods that have lower energetic requirements.